Behavior of Indonesian Muslim Immigrants in Consumsion Halal Products: a Case Study in Jinjang, Kuala Lumpur - Faiq Ahmad Rifani Siregar; Fatkhur Rohman Albanjari; Muslich Candrakusuma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes halal consumption behavior among Indonesian Muslim immigrants in Jinjang, Kuala Lumpur, Malaysia. Using a qualitative method with a case study approach, data was collected through surveys and interviews. The results showed that 67% of immigrants pay attention to the halal logo, and 58% read the ingredients before purchasing. However, many still have difficulty distinguishing between official and non-official halal logos, as well as low halal awareness among immigrant children. The implications of this study highlight the need for further socialization on halal and food safety, especially for children, as well as increasing halal literacy in immigrant communities. With increased awareness and understanding, it is expected that halal consumption practices can be more consistent and help create a more secure halal food ecosystem.